ANALISIS KANDUNGAN UNSUR HARA PUPUK ORGANIK CAIR DARI LIMBAH RUMAH TANGGA DI KABUPATEN MERAUKE - Wahida Wahida; Ni Luh Sri Suryaningsih (AGRICOLA, 2016)
Household waste is gained from household activities. The waste is divided into the form of organic waste and nonorganic waste. The organic waste is divided again into wet organic waste and dry organic waste. Wet organic waste comes from vegetables, fruits, fish, and shrimp. These wastes can be recycled into liquid organic fertilizer. This study aims to determine the content of nutrient from liquid organic fertilizer from household waste. Anaerob bacteri is involved in the process of organic fertilizer fermentation. The results showed that liquid fertilizer from household organic waste contains macro and micro nutrients, there are 7.85% of C-Organic, 0.33% of N-Total, 2.98% P2O5, 3.28% K2O, 1.98% Ca, 2.66% Mg, 212 ppm Fe, 0.852 ppm Mn, 118 ppm Na, and 169 ppm Zn.